The improving efficiency frontier of religious not-for-profit hospitals. - Harrison JP; Sexton C (Hospital Topics)
By using data-envelopment analysis (DEA), this study evaluates the efficiency of religious not-for-profit hospitals. Hospital executives, healthcare policy makers, taxpayers, and other stakeholders benefit from studies that improve hospital efficiency. Results indicate that overall efficiency in religious hospitals improved from 72% in 1998 to 74% in 2001. What is more important is that the number of religious hospitals operating on the efficiency frontier increased from 40 in 1998 to 47 in 2001. This clearly documents that religious hospitals are becoming more efficient in the management of resources. From a policy perspective, this study highlights the economic importance of encouraging increased efficiency throughout the healthcare industry. Copyright © by Helen Dwight Reid Education Foundation.